129k views
5 votes
Please give me the answer for a) and b)

Please give me the answer for a) and b)-example-1

1 Answer

2 votes

Answer: a) y=x²+6x+2 b) x=-3-√7, -3+√7

Explanation:

(0,2) (-6,2) (-3,-7)

a)

y=ax²+bx+c

(0,2)

x=0 y=2

⇒ 2=a(0²)+b(0)+c

⇒ 2=0+0+c

⇒ 2=c

(-6,2)

x=-6 y=2

⇒ 2=a(-6)²+b(-6)+2

⇒ 2=36a-6b+2

⇒ 2-2=36a-6b+2-2

⇒ 0=36a-6b

⇒ 0+6b=36a-6b+6b

⇒ 6b=36a

Divide both parts of the equation by 6:

b=6

(-3,-7)

⇒ -7=a(-3)²+6(-3)+2

⇒ -7=9a-18+2

⇒ -7=9a-16

⇒ -7+16=9a-16+16

⇒ 9=9a

Divide both parts of the equation by 9:

1=a

Hence,

y=x²+6x+2

b)

x²+6x+2=0

D=(-6)²-4*1*2

D=36-8

D=28

√D=√28

√D=√(4*7)

√D=2√7

x=(-6±2√7)/2

x=-3-√7

x=-3+√7

User Connel
by
4.8k points